Peningkatan Pengetahuan Perilaku Hidup Bersih dan Sehat Mental Masyarakat Kalurahan Timbulharjo, Sewon, Bantul di Era New Reality Covid-19 - Khoiriyah Isni; Ardarina Delfiona Kekasi; Nur Safani Indriani; Juwita Sari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The low level of public awareness in Balong Hamlet, Bibis Hamlet, and Kowen 2 Hamlet, Timbulharjo Village, Sewon, Bantul regarding clean and healthy living habits, both before and during the COVID-19 pandemic. The purpose of this community empowerment activity is to provide education about clean and healthy living habits and mental health so that there is an increase in public knowledge and awareness. This activity is carried out using the lecture, question and answer method, and case studies. This activity is carried out in three stages: the preparation stage, the implementation stage, and the reporting stage. The activities were carried out on 15, 16, and 17 February 2021, involving 70 people and three students. The results of this empowerment activity are evidenced by the existence of community empowerment which is shown through increasing knowledge about clean and mentally healthy living behaviors (p-value = 0.000). Education with the theme of clean and mentally healthy living habits needs to be carried out regularly to remind people of preventing Covid-19. Besides, it can also prevent public boredom in implementing clean and mentally healthy living behaviors.